2000
DOI: 10.1046/j.1471-4159.2000.741106.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated N1‐Acetylspermidine Levels in Gerbil and Rat Brains After CNS Injury

Abstract: Abstract:The polyamine system is very sensitive to different pathological states of the brain and is perturbed after CNS injury. The main modifications are significant increases in ornithine decarboxylase activity and an increase in tissue putrescine levels. Previously we have shown that the specific polyamine oxidase (PAO) inhibitor N 1 ,N 4 -bis(2,3-butadienyl)-1,4-butanediamine (MDL 72527) reduced the tissue putrescine levels, edema, and infarct volume after transient focal cerebral ischemia in spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Another metabolomic study [24] reported an increased level of a “biogenic amine” in the urine of PD patients; however, the identity of this amine was not described. As mentioned previously, N8-acetylspermidine is an excretion product; increases in PA excretion are associated with injury, including traumatic brain injury, as well as neuroinflammation and neuronal cell death [31,33,34]. Additionally, N8-acetylspermidine was shown to increase dopamine production in PC12 cells [35].…”
Section: Discussionmentioning
confidence: 98%
“…Another metabolomic study [24] reported an increased level of a “biogenic amine” in the urine of PD patients; however, the identity of this amine was not described. As mentioned previously, N8-acetylspermidine is an excretion product; increases in PA excretion are associated with injury, including traumatic brain injury, as well as neuroinflammation and neuronal cell death [31,33,34]. Additionally, N8-acetylspermidine was shown to increase dopamine production in PC12 cells [35].…”
Section: Discussionmentioning
confidence: 98%
“…Brain 3-aminopropanal levels continue to increase for at least 25 h after the onset of ischemia, a time frame that corresponds to the development of spreading brain cell death. Structurally distinct inhibitors of PAO attenuate the activity of brain PAO, prevent the production of 3-aminopropanal, and significantly protect against the development of ischemic brain damage in rat models of focal cerebral ischemia and head trauma (1,(3)(4)(5).…”
mentioning
confidence: 99%
“…Accumulating evidence has indicated that mammalian Ssat1 is also involved various physiological and pathological events, including liver regeneration [6], ischemia-reperfusion injury [7], [8], [9], pancreatitis [10], [11], lipid metabolism [12], [13], carcinogenesis [14], cell migration [15], and hypoxia signaling [16], through its ability to modulate polyamine content or by directly interacting with other protein effecters, such as hypoxia inducible factor 1-α (Hif-1α) and integrin α9. Moreover, the regulation of Ssat1 is as versatile as its functions, occurring at multiple levels including transcription [17], [18], mRNA processing [19], [20], [21], translation [22], and protein stabilization [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%